2015
DOI: 10.4081/cp.2015.777
|View full text |Cite
|
Sign up to set email alerts
|

Giant Dural Supratentorial Chondroma Generating the Question of How Large Can a Tumor Become without Revealing Itself

Abstract: Chondromas usually affect the small bones of hand and feet and account for only 0.5% of all intracranial tumors. We present a case of a giant, supratentorial meningeal chondroma in a 19-year old male patient and discuss the preoperative diagnostic findings as well as the appropriate treatment options. A 19-old male presented with headache, new onset of focal seizures and paresis of left upper extremity. Magnetic resonance imaging revealed a large right parietal tumor in the precentral region with local mass ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…The mononucleated cells were enclosed within a chondroid matrix, with no signs of atypia or mitotic activities. Unlike in our case, other studies further performed immunohistochemistry and reported no immunoreactivity for Ki‐67 . Thus, it could be more useful for differentiating chondroma from malignant tumor such as chondrosarcoma or metastasis.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The mononucleated cells were enclosed within a chondroid matrix, with no signs of atypia or mitotic activities. Unlike in our case, other studies further performed immunohistochemistry and reported no immunoreactivity for Ki‐67 . Thus, it could be more useful for differentiating chondroma from malignant tumor such as chondrosarcoma or metastasis.…”
Section: Discussioncontrasting
confidence: 52%
“…Intracranial chondroma is a very rare benign cartilaginous tumor with estimated incidence of 0.2% to 0.3% . It mainly arises from the skull base, where it originates from spheno‐petrosal, spheno‐occipital as well as petro‐occipital synchondroses, and seldomly arises from the falx, the dural convexity, or the choroid plexus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They occur intracranially in rare cases with an estimated incidence of 0.2% to 0.5% of all intracranial neoplasms [2]. On the contrary, Connelly et al [3] described less than 30 reported cases in 2018 and found that these lesions can rarely be seen in the parasellar region, at the falx, or arousing from the dura convexity [4].…”
Section: Introductionmentioning
confidence: 99%

Intracranial Dural Chondroma: Case Report and Review of Literature

Napoleao IMBUNHE,
Yao Christian Hugues DOKPONOU,
Fresnel Lutece Ontsi OBAME
et al. 2023
World J. Adv. Res. Rev.
“…1,2 Intracranial chondromas account for 0.2% of all intracranial tumors and were first reported by Hirschfeld in 1851. [3][4][5][6][7][8][9] Rarely, intracranial chondromas can arise from the falx, and we present a middle-aged woman with such a condition. 6,7,10…”
mentioning
confidence: 99%